Clinical Supervision and Its Impact on Pedagogical Competence of Vocational School Teachers - Sari, Emilia; Masduki, Ahmad; Matin, Matin (Journal of Education Reseach and Evaluation, 2021)
Teachers must have the competences for the implementation of quality education. Therefore, teachers' quality of learning in the classroom has become the teachers' duty and responsibility. This study aims to explore the information about the effect of clinical supervision and self-efficacy on teacher pedagogic competence. The research site is at State Vocational High Schools. This study used a survey method with path analysis techniques and a causal quantitative approach, and the sample was 72 teachers using a simple random sampling technique or simple random sampling. The teacher who became the object of the research was determined using the sample technique formula from Slovin. The data analysis technique was performed using descriptive and inferential statistics by first doing the prerequisite analysis test, namely population normality and regression analysis. The study's findings show that school principals' success in the clinical supervision process will determine teachers' pedagogical competence. Competent teachers can learn well and increase student learning motivation to achieve and produce students who excel in their fields. This clinical supervision can be performed if carried out in the right and proper way. The school principal as a supervisor in the implementation of clinical supervision must promote togetherness, where the problems faced by teachers are joint problems that must resolve together.